Microinsurance to Mitigate Poverty in Malaysia - Shamshul Afendi, Alisa; Jacob, Kavikumar (Enhanced Knowledge in Sciences and Technology, 2023)
Access to high-quality, low-cost financial services and products is critical for eliminating imbalanced economic status and poverty. Microinsurance is one of the products that can be recognized as one of the techniques for reducing low-income segment vulnerability. This study aims to determine the importance of microinsurance in mitigating poverty and the relationship between the two. The approach used in this research is an exploratory study by a survey. This study revealed that most low-income households could not afford insurance, while households from M40 and T20 had no problem owning insurance. Furthermore, this study shows that the microinsurance scheme is vital for households of B40 as these people often have difficulties due to financial burdens